A study on concrete using waste plastic as aggregates - Rohaya Binti, Abd Wahab (Universiti Malaysia Sarawak (UNIMAS), 2008)
In Malaysia, most of plastics waste is abandoned and not recycled. This situation causes serious problems such as wastage of natural resources and environmental pollution. Solid waste management is one of the major environmental concerns in the world. In fact wide variety of waste materials can be utilized as inert in cement matrix. In this research, bottle plastics are used as plastics waste as fine aggregates. The aim of this work is to study the workability and strength of plastics waste as the replacement of fine aggregate in concrete. This study involved 3 tests to determine the competence of reusing waste plastic in the production of concrete. Waste plastic was used as a partial replacement for sand by 0%, 10%, 15%, and 20% with concrete mixtures. These tests include performing slump, compressive strength, and splitting tensile strength. 24 cubes were molded for compressive strength and 24 cylinders were cast for splitting tensile strength. Curing ages of 7, 14, and 28 days for the concrete mixtures were applied in this work. This study insures that reusing waste plastic as a sandsubstitution aggregate in concrete gives a good approach to reduce the cost of materials and solve some of the solid waste problems posed by plastics.